THE EFFECTIVENESS OF "TASLIMA" METHOD IN OPTIMIZING THE QUALITY OF AL-QUR’AN MEMORIZATION ON LONG-TERM MEMORY RETENTION - Syahidah, Mega; Hina, Shahzadi; Qodriyah, Khodijatul (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
Abstract:This study aims to examine the effectiveness of Tasmi’ method per multiple of five juz (Taslima) in optimizing the quality of Al-Qur'an memorization in strengthening long-term memory retention. The method used in this study is descriptive qualitative with a case study approach, which focuses on the experiences of Al-Qur'an memorizers who apply the Taslima method in their memorization. Data were collected through in-depth interviews with memorizers, ustadz/ustadzah and Tasmi’ mentors, as well as direct observation of the Tasmi’ process carried out at the Tahfidzul Al-Qur'an Islamic Boarding School (PPTQ) in Malang City. The results of the study showed that the Taslima method had a significant influence on the quality of memorization, especially in terms of the memorizer's ability to maintain memorization in a long-term. Repetition of memorization per multiple of five juz has been shown to facilitate the process of memory consolidation and reduce excessive memorization burden, so that long-term memory can be maintained more effectively. In addition, multisensory involvement through hearing and pronunciation also increases memory strength. Regular review process (muroja’ah) and direct feedback from the ustadz/ustadzah strengthen the understanding of the meaning and ensure the quality of memorization is maintained. This study concludes that the Taslima method is one of the effective approaches in strengthening long-term memory retention, which can improve the overall quality of memorization of the Qur'an.